The Role of NGOs In the Resolution of The Ongoing Anglophone Conflict From 2016 To 2021 - Pippie Hugues (Zien Journals, 2021)
The gruesome and perpetual violation of human rights in Cameroon is alarming and a call for concern especially from 2016 to 2021 during the ongoing Anglophone conflict. The government has tried to curb human rights violation in the country but its measures seem ineffective. This has caused the researcher to investigate the role played by Non-Governmental Organisations (NGOs) in the resolution of the ongoing conflict. A detailed study and interviews done on the activities of some selected NGOs who have been very active in monitoring, documenting and reporting issues of the conflict was carried out. Findings reveal that they have recorded greater achievements in their role by bringing to the lamplight the situation of human rights violations in the country despite the numerous challenges they face in their functioning. Based on the findings, the paper highlights some positive policy recommendations that may help improve their important role in conflict resolution.
Keywords: highlights; perpetual; Cameroon; alarming